Circular RNAs in the Central Nervous System - Li, Meng-Lan; Wang, Wen; Jin, Zi-Bing (Frontiers in Molecular Biosciences, 2021)
Circular RNAs (circRNAs) are endogenous single-stranded RNAs characterized by covalently closed loop structures with neither 5' to 3' polarity nor poly(A) tails. They are generated most commonly from back-splicing of protein-coding exons. CircRNAs have tissue-specific distribution and are evolutionarily conserved, and many circRNAs play important biological functions by combining with microRNAs and proteins to regulate protein functions and their own translation. Numerous studies have shown that circRNAs are enriched in the central nervous system (CNS) and play an important role in the development and maintenance of homeostasis. Correspondingly, they also play an important role in the occurrence and progression of CNS diseases. In this review, we highlight the current state of circRNA biogenesis, properties, and function and the crucial roles that they play in the CNS.